Introduzione allo studio della partecipazione politica (1966) - Alessandro Pizzorno (Quaderni di Sociologia, 2019)
The indicators currently employed in research on politicai participation show that this concept is usually restricted to a certain kind of participation. This is probably due to the fact that these studies are framed as answers to the problem of consensus. But participation does necessarily identify with consensus or dissent. On the contrary the modern problem of participation originates with the autonomous rise of the civil society and the transposition on the political plane of its own conflicts. Participation may become then the product of the effort to overthrow or maintain the system of inequalities of the civil society. These premises lead us to take into consideration a non govenwnental dimension of political participation. The American political science has been the first to get rid of the excessively narrow concept of state. Now, however, the notion of political system appears to impose again to the political activity limits that do not allow to account for the universalistic elements it contains. It seems therefore more convenient to view the political acrion – in the modern world – as specific of the two kinds of solidarity grown from the formation of the Nation-state and from the class struggle. This subdivision corresponds also to the two major models with which the conditions of political participation have been explaned: namely the model of class consciusness and the one definable as «center-periphery». Each of these models accounts for certain facts only. If we analyse them, however, they seem to contain a common principle, that we could express with the proposition that participation is possible only within certain «areas of equality». More specific propositions can in turn be formulated, when different types of participation are taken into consideration. By crossclassifying the two dimensions of (1) statual-extra statual, and (2) prevailing private or political solidarity, four types are proposed: political professionalism, civic participation, social movements and subcultures. Finally the data from recent reserches are examined, with a particular effort to delineate some peculiarities of the Italian situation. Notable in it the relevance of subcultural participation and of the residual social movements and the lesser importance of civic participation.